Contemporary approach to cardiogenic shock care: a state-of-the-art review - Mehta, Aditya; Vavilin, Ilan; Nguyen, Andrew H.; Batchelor, Wayne B.; Blumer, Vanessa; Cilia, Lindsey; Dewanjee, Aditya; Desai, Mehul; Desai, Shashank S.; Flanagan, Michael C.; Isseh, Iyad N.; Kennedy, Jamie L. W.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Cardiogenic shock (CS) is a time-sensitive and hemodynamically complex syndrome with a broad spectrum of etiologies and clinical presentations. Despite contemporary therapies, CS continues to maintain high morbidity and mortality ranging from 35 to 50%. More recently, burgeoning observational research in this field aimed at enhancing the early recognition and characterization of the shock state through standardized team-based protocols, comprehensive hemodynamic profiling, and tailored and selective utilization of temporary mechanical circulatory support devices has been associated with improved outcomes. In this narrative review, we discuss the pathophysiology of CS, novel phenotypes, evolving definitions and staging systems, currently available pharmacologic and device-based therapies, standardized, team-based management protocols, and regionalized systems-of-care aimed at improving shock outcomes. We also explore opportunities for fertile investigation through randomized and non-randomized studies to address the prevailing knowledge gaps that will be critical to improving long-term outcomes.